In‐situ formation of an efficient trimetallic (CuZnAg) electrocatalyst for water oxidation. (12th October 2020) - Akbar, Muhammad; Shah, Afzal; Iftikhar, Faiza Jan; Ali, Ghulam; Han, HyukSu; Rahman, Gul
Summary: There is a need to develop highly efficient electrocatalysts based on non‐noble metals which can be used for water splitting. Thus, to realize an acceptable oxygen evolution reaction (OER) performance, a combination of non‐noble metals was used to improve the architecture and conducive to a facile OER. For this purpose, a binder‐free and non‐noble metal‐based trimetallic (CuZnAg) composite OER a electrocatalyst was grown at the surface of fluorine‐doped tin oxide by a facile one step in‐situ electrodeposition method using chronoamperometry. The formation and performance of the catalyst were ensured from XRD, SEM, EDX, chronoamperometry, and linear scan voltammetry. The trimetallic composite showed good results toward OER in 1 M KOH electrolyte at pH 13 at a current density of 1 mA/cm 2 with an overpotential of 303 mV at a scan rate of 10 mV/sec. The results revealed robust electrochemical durability under alkaline conditions and the electrocatalyst holds great promise for OER. Abstract : A novel and efficient water splitting electrocatalyst made up of CuZnAg was synthesized by a facile and low‐cost method.